Determination of suitable recreational areas in Adana Province Cukurova district by AHP technique - Nurhan Koçan; Şeyma Şengür; Muhibe Aslı Alp; Ömer Lütfü Çorbacı; Esra Çetinkaya Özkan (Journal of Environmental Engineering and Landscape Management)
Recreation is people’s whole activity to regain their lost energy. In urban recreation areas, today’s people can escape city life and reach themselves and nature at some point. In this context, the distribution, size, and accessibility of recreation areas in cities gain importance. The research aims to determine potential recreation areas by considering the natural and physical characteristics of the Adana Province Cukurova district.